Rezső Milleker and political geography - Dövényi, Zoltán; Perényi, Bálint (Acta Geographica Debrecina Landscape & Environment series, 2021)
This paper aims to examinate and to present the political geographical work of Rezső Milleker. Although political geography was not his main specialty, time to time he tried to create something of scientifical value in this field of science, but the attention of professional circles and the success avoided him. By evaluating these works we try to answer the question, where his place was in Hungarian political geography between the two world wars.